Spiritual Work Motivation as a Mediator in the Relationship Between Organizational Climate and Teacher Performance - Purwanto, Eko Sigit; Haryanti, Nik (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the role of spiritual work motivation in mediating the influence of organizational climate on teacher performance. This study uses a quantitative approach with an explanatory method. The variables studied include spiritual work motivation, organizational climate, and teacher performance. Data were collected by distributing questionnaires to 100 teachers in one of the state madrasahs in Tulungagung, which were selected using random sampling techniques. Data analysis was carried out using Smart PLS software's Partial Least Squares (PLS) method. The study results indicate that organizational climate positively affects teacher performance, which is supported by this finding. In addition, teacher performance also has a positive effect on spiritual work motivation. Furthermore, spiritual work motivation is proven to mediate the positive influence between organizational climate and teacher performance. This finding indicates that good work climate conditions, recognition, and motivation teachers receive can encourage their performance improvement. With a supportive climate, teachers feel more motivated to develop their competencies, thereby improving the quality of their work.